Mineralogical and Geochemical Clay Analysis for Portland Cement Quality Distribution: A Study Case From Ajibarang District, Central Java, Indonesia - Abidin, Izdihar Sahda; Siswandi; Gibran, Akhmad Khahlil (UIR PRESS, 2024)
Nowadays, the development of infrastructure has caused an increase in the need for cement. To determine the suitability of the raw materials used in cement production, an assessment must be carried out on the quality anMineralogical and Geochemical Clay Analysis for Portland Cement Quality Distribution: A Study Case From Ajibarang District, Central Java, Indonesiad suitability of the cement raw materials. This research was conducted in Halang Formation of the Tipar Kidul area and around Banyumas Regency, Central Java. The methods used are X-ray fluorescence (XRF) and scanning electron microscopy (SEM). Data from XRF analysis generally shows SiO2 values from 26.83% to 57.75%, Al2O3 values from 11.18% to 20.23%, and Fe2O3 values from 3.21% to 8.76%. Judging from the aluminum index (AI) content, the ideal cement raw materials are two samples with a proportion of 3.17% to 3.22%. The results of SEM analysis show that there are illite, calcite, quartz and smectite minerals in the claystone research area. Based on data, almost 75% of the claystone survey area was found to be suitable as a raw material for cement. This research has a positive impact on the characterization of limestone as a raw material for cement by utilizing geochemical analysis and electron microscopy to achieve a more comprehensive understanding of the evaluation of limestone quality.